PERAN GURU DAN STRATEGI PEMBELAJARAN DALAM MENGELOLA ANAK ADHD (ATTENTION DEFICIT HYPERACTIVITY DISORDER) DI LINGKUNGAN PENDIDIKAN INKLUSI - Devi Fifi Tarigan; Widia Abisah Br Ginting; Vika Febrianti; Veranita Christy; Cinta Roulina Sigalingging; Yeni Marito (Cahaya Ilmu Bangsa Institute, 2024)
The research conducted aims to provide a clear picture of the challenges and strategies in teaching children with ADHD (Attention Deficit Hyperactivity Disorder) in an inclusive school environment. Data collection techniques in this study include interviews and observations. Through observation techniques to observe activities during learning activities of an ADHD student at SMPN 4 Binjai, as well as interviews Ed with one of the teachers to obtain in-depth information related to the research subject. The results obtained are that children with ADHD can actively participate and develop in the learning process, even though they face various challenges. Schools therefore have the potential to be supportive places for all students, including those with special needs.